Durum Wheat Yield and Grain Quality in Early Transition from Conventional to Conservation Tillage in Semi-Arid Mediterranean Conditions - Karima Djouadi; Arezki Mekliche; Sonia Dahmani; Nadia Insaf Ladjiar; Yasmine Abid; Zakaria Silarbi; Abdelmadjid Hamadache; Michele Pisante (Agriculture, 2021)
In semi-arid Mediterranean areas, there is a growing interest in adopting conservation tillage practices for their advantages in improving soils fertility, reducing production costs, and stabilizing crop yields. The aim of this study conducted in the 2019 and 2020 seasons was to investigate the effect of three tillage systems—conventional tillage (CT), minimum tillage (MT), and no-tillage (NT)—on grain yield, yield components, and quality indices of a durum wheat crop (Triticum durum Desf. cv. Simeto) grown in monoculture in semi-arid conditions of Northern Algeria. Tillage systems had a significant effect on the average yield of the 2 years, with NT being 28% and 35% higher than CT and MT, respectively—a trend even more evident in the second year under observation. The superiority of NT (p < 0.001) in the second year (2020) is mainly due to the increased spikes density (318.93 spikes m2 under NT vs. 225.07 and 215.20 spikes m2 under MT and CT, respectively). Yield components and quality parameters were more affected by climatic conditions than by tillage treatments. The number of kernels per spike being the most affected by water and heat stresses occurred in 2020 season. A decrease of 51% is noted regardless of the tillage treatment, which negatively affected the grain yield in that year (1.9 vs. 1.3 t ha−1 in 2019 and 2020, respectively). This stress also induced an increase in grain protein content, but a reduction of its weight. The results of this study conducted in the early transition from conventional to conservation tillage show that durum wheat grown under NT results in higher grain yield than the other systems in the specific operative conditions of the study region, providing better seed emergence and better spikes density, especially in the dry years. Moreover, the quality parameters are more affected by weather conditions than by the tillage system—with an interaction year × tillage system significant only for the grain.